Spectrum of mast cell activation disorders. (June 2014) - Petra, Anastasia I; Panagiotidou, Smaro; Stewart, Julia M; Conti, Pio; Theoharides, Theoharis C
<x xml:space="preserve">Abstract</x> Mast cell (MC) activation disorders present with multiple symptoms including flushing, pruritus, hypotension, gastrointestinal complaints, irritability, headaches, concentration/memory loss and neuropsychiatric issues. These disorders are classified as: cutaneous and systemic mastocytosis with a c-kit mutation and clonal MC activation disorder, allergies, urticarias and inflammatory disorders and mast cell activation syndrome (MCAS), idiopathic urticaria and angioedema. MCs are activated by IgE, but also by cytokines, environmental, food, infectious, drug and stress triggers, leading to secretion of multiple mediators. The symptom profile and comorbidities associated with these disorders, such as chronic fatigue syndrome and fibromyalgia, are confusing. We propose the use of the term 'spectrum' and highlight the main symptoms, useful diagnostic tests and treatment approaches.